Effect of urban street canyon aspect ratio on thermal performance of road pavement solar collectors (RPSC) - Nasir, Diana S.N.M.; Hughes, Ben Richard; Calautit, John Kaiser; Aquino, Angelo I.; Shahzad, Sally (Elsevier, 2017)
Studies on RPSC (road pavement solar collectors) have shown the potential of reducing the urban heat island effect by dissipating the heat from the pavement for energy harness. In our previous work, performance analysis of RPSC system was carried out to compare the RPSC embedment in two scenarios; within an urban street canyon and within suburban or rural area. The current study expands the analysis of the RPSC system in urban areas by assessing the impact of varying canyon aspect ratios on the performance of RPSC. De-coupled Computational Fluid Dynamic (CFD) approach was proposed to investigate the integration of RPSC system in an urban canyon. The CFD tool ANSYS Fluent 15.0 was used to simulate the fluid flow and heat transfer on the pavement/road surface by enabling three models: (i) energy model, (ii) standard k-epsilon model, and (iii) coupled DO-solar load radiation model. The results showed that a significant pavement surface temperature increase was found when the aspect ratio (AR) was increased from 1 to 2 while minimal increase was observed for the canyon with AR above 2. At the particular simulated time (13:00) and location, it was found that the overall performance of the RPSC system significantly increased by up to 13.0 when AR was increased from 1 to 2, but the performance of RSPC in shadow area (due to the shading effect of building) had significantly dropped (up to 30.0) from AR 3 to 4. Findings of this study showed that the canyon aspect ratio had a significant impact on the temperature distribution of the ground surface and should be taken into consideration when assessing the performance of RPSC in urban areas.